1993
DOI: 10.30541/v32i4iipp.713-723
|View full text |Cite
|
Sign up to set email alerts
|

A Micro Analysis of Demand-side Determinants of Schooling in Urban Pakistan

Abstract: Investment in human capital is as important for growth as physical capital. The objective of this paper is to establish the importance of some factors, that affect the decision of a household to send their children who are of school going age, between 5-14 years, to school in urban areas. This paper is divided into five sections, Section 2 reviews the relevant schooling literature for Pakistan. Section 3 points some theoretical hypotheses describing the data and Section 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…A decade ago many argued that enrollment rates in Pakistan were so low because of the overall weakness of demand (Birdsall, Ross, and Sabot 1993;Hamid 1993). More recent studies, however, have questioned this view and suggested that levels of demand are high but that governmental investment in primary schooling has been too low (World Bank 1996, as cited by Gazdar 1999).…”
Section: Primary Schooling In Pakistanmentioning
confidence: 95%
“…A decade ago many argued that enrollment rates in Pakistan were so low because of the overall weakness of demand (Birdsall, Ross, and Sabot 1993;Hamid 1993). More recent studies, however, have questioned this view and suggested that levels of demand are high but that governmental investment in primary schooling has been too low (World Bank 1996, as cited by Gazdar 1999).…”
Section: Primary Schooling In Pakistanmentioning
confidence: 95%
“…Analyzing the sample separately by sex is particularly important in Pakistan where evidence suggests that females receive less education than males (e.g. Bilquees and Hamid, 1989;Women in Pakistan, 1989;Burney and Irfan, 1991;Hamid, 1993;Sathar and Lloyd, 1993;Blood, 1995). 3 Appendix C also contains a correlation matrix of the variables for the full sample.…”
Section: B Datamentioning
confidence: 99%
“…Girls, in this view, maintain and carry the burden of 'respect' or izzat through restrictions on their mobility and circumscribed adherence to social conventions in terms of roles, behaviour, appearance and kinship relations. In this sense, socio-cultural norms of rural society in Pakistan have been acknowledged to have an adverse effect on girls' schooling (Hamid 1993) whereby reservations around 'respectability' come to the forefront of the decision-making equation around sending girls to school. Threats to respectability can stem from walking to school, coming into contact with men unrelated to them, and exposure of girls to ideas not in line with traditional gender roles expected of them.…”
Section: Girls' Education In Rural Pakistanmentioning
confidence: 99%
“…Pakistan's position within this global context of gender inequalities in education reflects dimensions of both infrastructural inadequacies to provide sufficient education to girls as well as societal values that place less weight on girls' schooling compared with boys' schooling. Attitudes towards girls' schooling are directly associated with cultural values that act as a deterrent to the encouragement of gender-equitable access to education (Hamid 1993). Rather than being viewed as an empowering choice by many parents, girls' education represents a broader index of cultural values, considerations of economic returns, notions of family integrity and gender ideals that, as we will explore, can often lead to ambiguity around the importance of girls being educated, and even an unfavourable attitude towards girls' education.…”
Section: Introductionmentioning
confidence: 99%